Managing chronic health needs in child care and schools : a quick reference guide - Donoghue, Elaine A.; Kraft, Colleen A. (American Academy of Pediatrics, 2019)
"This fully revised and updated resource helps teachers and caregivers address the challenges of caring for children with chronic health conditions and special health care needs in child care and school settings"--Publisher's description